Necropolitics as a Media Spectacle: Massacres in the Prisons of Ecuador - Brito Alvarado, Xavier (2023)
This article addresses the media narratives of the violence in Ecuadorian prisons in 2022. This essay has two methodological moments; the first encompasses a critique of the media discourses of violence from sociology, criminology, and communication;this intersection of epistemological perspectives allows us to weave various narratives of violence, fear, and death. In this context, the media build stories and position imaginaries that generate a public opinion that rejects persons deprived of liberty and government policies to combat crime. The second moment focuses on systematizing information published in the newspapers El Comercio and El Universo, newspapers with national circulation, in the last eleven months of 2022, to contrast the journalistic narratives about violence and deaths as a media spectacle, leading to think of this situation as a necropolitical scenario.